Penerapan Akad Ijarah Pada Sistem Sewa Menyewa Sawah (Studi Pada Desa Tanjung Agung Kecamatan Ulumusi Kabupaten Empat Lawang) - Puji Hastuti; Nurul Hak; Badaruddin Nurhab (ITB AAS INDONESIA Surakarta, 2022)
The purpose of this study is first, to find out the system of renting rice fields in Tanjung Agung Village, Ulumusi District, Empat Lawang Regency. Second, knowing the application of the ijarah contract to the rice field rental system in Tanjung Agung Village, Ulumusi District, Empat Lawang Regency. The type of research conducted is this research is a type of field research (field research) with a qualitative approach. Based on the results of the study, it can be concluded that first, the rice field rental system in Tanjung Agung Village, Ulumusi District, Empat Lawang Regency on rice farming land has become one of the activities carried out between land owners and tenant farmers to manage productive land. The application of leasing has existed for a long time, the agreement system is still mutual trust and mutual assistance. Second, the ijarah contract on the rice field rental system in Tanjung Agung Village, Ulumusi District, Empat Lawang Regency, the economic view according to sharia, the application of ijarah (lease in Islam) is still in accordance with Islamic provisions because the system helps each other. The application of leases on agricultural land based on the observations of academics and religious leaders is allowed as long as it is for the common good.